SERUM INSULIN AND CRP AS PREDICTORS OF GLYCEMIC CONTROL IN TYPE 2 DIABETIC PATIENTS - Arvind Kumar Gupta; Dr. Nikhil Rajak; Dr. Anurag Kesarwani; Simran Bamniya; Raashika Saxena (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a complex metabolic disorder characterized by insulin resistance and chronic low-grade inflammation. In India alone, over 72 million individuals currently live with diabetes, and this number is projected to nearly double by 2045. Objectives: In this study, we aimed to investigate the correlation between serum insulin and CRP levels with HbA1c in T2DM patients to assess their predictive value in determining glycemic control. Materials and Methods: A hospital-based cross-sectional observational study included on 100 T2DM patients aged 20-65 years. Fasting serum insulin and CRP levels were measured and correlated with glycemic status. Results: The results showed that poor glycemic control was significantly associated with elevated CRP and fasting insulin levels. Conclusion: These findings suggest that insulin resistance and inflammation play pivotal roles in the pathophysiology of T2DM and that CRP and insulin may serve as useful biomarkers in predicting glycemic control.